Association between nutritional status of scheduled caste children and their educational performance in rural Barabanki district, Uttar Pradesh, India - Ramu Rawat; Sayeed Unisa (Elsevier, 2021)
Aim: In this study we investigate the association between children nutritional status and their educational performance in rural areas. Methods: A cross-sectional study was designed to investigate the association in children nutritional status and their educational performance. The study was conducted among 313 school going children (aged 6-14 years) from 300 Scheduled Caste households in the rural Barabanki district of Uttar Pradesh, 2017. Results: In this study, about 53% boys and 47% girls aged 6-14 years were participated. Children nutritional status and their educational performance, i.e. reading, writing and math, were analyzed. It was found that children studying in the same standard but their educational abilities varies widely. The children educational performance were increased with their years schooling especially in reading and writing. However, the estimates revealed that healthy children (not-stunted & not-wasted) were performing better (in medium & high categories) as compared to malnourished. Further, multivariate results show a significant association between child health and their educational performance. Conclusion: The study statistics revealed that the children health is a significant input for their educational performance. The government has various programs for child health and education; still malnutrition to be continues high. It has been recognized that better governance is necessary for effective function of any programs. Therefore, appropriate community-based intervention should be designed to address the problem of child health and possible nutritional outcomes and school performance of the children.